Digenetic trematodes of marine fishes from Kuwaiti Coast of the Arabian Gulf - Al-Yamani; Nahhas, F. M. (Kuwait Bulletin of Marine Science, 1981)
During July and August 1978, 165 fishes belonging to 35 species in 19 families were collected from the Kuwaitai coast of the Arabian Gulf and examined for parasites. Nine digenetic trematodes including three new species and two new genera are described from the following families: Hemiuridae-Opisthadena kuwaiti, n. sp. from Valamugil seheli; Lecithocladium bulbobrum Reid, Coil and Kuntz, 1966 from Johnius aneus (new host record): clupenuroides sheemi n.g., n.sp. from Eleutheronema tetradactylum; Angiodactylidae - Hexangium sigani Goto and Ozaki, 1929 from Siganus oramin; Pleorchiidae- Pleorchis arabicus n.sp. from Otolithes argenteus; Opecoelidae - Helicometrina nimia Linton, 1910, from Nemipterus tolu (new host record) and Plagioporus sp. from Nemipterus tolu; Acanthocolpidae - Stephanostomum sp. from Lutjanus coccineus. Keys to the species of Opisthadena and Pleorchis, and to certain closely related dinurid genera are given. Pleorchis puriensis Gupta and Ahmad, 1976 is transferred to the new genus Parapleorchis.
Not yet entered.